Psoralen analogues: synthesis, inhibitory activity of growth of human tumor cell lines and computational studies - Oliveira, Ana M. A. G. (2006)
Eight psoralens have been evaluated for their ability to inhibit the in vitro growth of three human turner cell lines representing different tumor types, MCF-7 (breast cancer), NCI-14460 (non-small cell lung cancer) and SF-268 (CNS cancer). The synthesis of four new psoralens (benzofur-ocournarins) is presented as well as the results of the ab initio calculations to find the parameters that relate the structure with the antitumor activity. This work provides supplementary information that could allow the development of new psoralen analogues with this type of biological activity.